Dion Boucicault’s Robert Emmet?: the question of authorship and the season premiere at the McVicker's Theatre, Chicago, on November 5, 1884 - Fernanda Korovsky Moura (Ilha do Desterro)
The Irish playwright Dion Boucicault (1820-1890) spent most of his career in the United States, where he established himself, adapting crucial moments of Irish history to the stage. Robert Emmet (1884), a play produced at the end of his career, arouses questioning surrounding its authorship. The dramatic text was arguably written by the playwright Frank Marshall (1840-1889) at the request of the actor Henry Irving (1838-1905). This paper explores the question of Robert Emmet’s authorship and investigates the reception of the production in its unsuccessful opening season at the McVicker’s Theatre in Chicago in November, 1884, and Boucicault’s part in it.